Pengaruh Pendapatan Asli Daerah dan Dana Bagi Hasil Terhadap Pertumbuhan Ekonomi Melalui Belanja Langsung di Provinsi Kalimantan Selatan - Astriana, Putri; Siregar, Syahrituah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
This research examines how Regional Original Income and Profit Sharing Funds influence Economic Growth through Direct Expenditure. Secondary data collected in districts/cities in South Kalimantan Province for fifteen years, from 2008 to 2022, was used in this research. The official website of the South Kalimantan Provincial Government, especially the South Kalimantan Central Statistics Agency, provides information for this study. Path analysis and Sobel test are the analysis techniques used in this research. The findings of this research indicate that Original Regional Income and Profit Sharing Funds have a positive effect on Direct Expenditure, Original Regional Income and Direct Expenditure have no effect on economic growth. Meanwhile, Profit Sharing Funds influence economic growth. Direct Expenditure is able to influence or intervene in Regional Original Income and Profit Sharing Funds on Economic Growth.